Formação inicial de professores e dispositivo grupal: compondo processos formativos - Debus, Ionice da Silva (2013)
This dissertation forms part of the Line Formation, Knowledge and Professional Development Post-Graduate Program in Education, of Federal University of Santa Maria. Taking as reference the formative experience of the Group of Studies and Research in Social Education and Imaginary GEPEIS, through the device group, we performed the research that has as study objective the Undergraduate Supplementary Discipline (elective) denominated Groupal Device and Teacher Formation, offered to Pedagogy course (diurnal) of the same university. The methodology employed was cartography, in which, through the observations of the participants, the group experiences, the narratives seized and records in the gradebook, configure the data of this research. In theoretical, about the formation issues we start from Ferry (2004); Nóvoa (2009), the theories of group Pichin-Rivière (1998), Barros (2009); Souto (2003), Fernandez (2006); Bleger ( 1998); Quiroga (1989), Oliveira (2006, 2009). For data analysis was used the hermeneutics approach from Delory-Momberger (2008); Gadamer (2008). Thus, the collective production of subjectivities processes around the formation of future teachers, and the group as a formation device, especially the importance of the teaching practice, shaped the study. Composing these processes, such as cartographic exercise meant much more than search : instigated and involved researchers and researched around the reflection of "place" of Groupal Device and its importance to teacher formation. Therefore, the context in which the formation of academics occurred in relation to theories of group, considering the complexity of this space, was permeated with significant learning related to the importance of this knowledge the groupal device - for the formation of teachers, school and Education.